Platelet-rich clots as identified by Martius Scarlet Blue staining are isodense on NCCT. (5th April 2019) - Fitzgerald, Sean T; Wang, Shunli; Dai, Daying; Douglas, Andrew; Kadirvel, Ramanathan; Gounis, Matthew J; Chueh, Juyu; Puri, Ajit S; Layton, Kennith F; Thacker, Ike C; Hanel, Ricardo A; Sauvageau, Eric; et al.
Abstract : Background: Current studies on clot characterization in acute ischemic stroke focus on fibrin and red blood cell composition. Few studies have examined platelet composition in acute ischemic stroke clots. We characterize clot composition using the Martius Scarlet Blue stain and assess associations between platelet density and CT density. Materials and method: Histopathological analysis of the clots collected as part of the multi-institutional STRIP registry was performed using Martius Scarlet Blue stain and the composition of the clots was quantified using Orbit Image Analysis (www.orbit.bio) machine learning software. Prior to endovascular treatment, each patient underwent non-contrast CT (NCCT) and the CT density of each clot was measured. Correlations between clot components and clinical information were assessed using the χ 2 test. Results: Eighty-five patients were included in the study. The mean platelet density of the clots was 15.7% (2.5–72.5%). There was a significant correlation between platelet-rich clots and the absence of hyperdensity on NCCT, (ρ=0.321, p=0.003*, n=85). Similarly, there was a significant inverse correlation between the percentage of platelets and the mean Hounsfield Units on NCCT (ρ=−0.243, p=0.025*, n=85). Conclusion: Martius Scarlet Blue stain can identify patients who have platelet-rich clots. Platelet-rich clots are isodense on NCCT.